Diagnóstico de assimetrias laterais dos membros inferioresem jogadores de futebol por meio de variáveis biomecânicas e de testes motores - Cristiane Bhering Moretzsohn Silva (2010)
The aim of the study was to compare of biomechanical and motor tests for the identification of bilateral asymmetries of the lower limbs of soccer players. The biomechanical tests were squat and countermovement jumps on a double force platform where impulse, peak power and peak ground reaction force were determined. The motor tests consisted of a single hop test for distance as squat and countermovement jump. This test is related in the literature as an adequate method to identify lateral asymmetries after anterior cruciate ligament reconstruction. 59 malesoccer players (36 under-13 and 23 juniors players) participated in this study. A symmetry index was calculated for all variables as follows: (performance of the right leg performance of the left leg) / best performance) X 100. Differences of more than 15% between the legs were considered relevant differences. In order to compare the results of the biomechanical and motor tests, correlations between the bilateraldifferences of biomechanical variables and jump distances were determined. Furthermore, Contingency Coefficients were calculated between the relevant lateral differences (>15%) determined by biomechanical variables and by the performance of the jump tests. The results showed that the biomechanical variables are more severe criteria for the identification of lateral differences than the performance of the motor testes. Significant correlations (0,49 0,51, p<0,05) of lateral differences between biomechanical variables (peak power, impulse, maximal force) and jump performance were only detected for the countermovement jump of the under-13. This means that lateral differences of the biomechanical variables and the lateral differences of jumping performance have only about 25% of common variance. Nosignificant correlations were found for the juniors players. Therefore, it can be concluded that the single hop test for distance might be an adequate method for the diagnosis of great lateral differences as found after anterior cruciate ligament reconstruction. However, if lateral differences are rather small, biomechanical variables are more sensitive for the assessment of lateral differences. Vertical jumps on a double force platform should be applied during the training process in order toprevent the development of relevant lateral asymmetries which may increase injury risk.